Canakinumab is effective in patients with familial Mediterranean fever resistant and intolerant to the colchicine and/or anakinra treatment - DURUÖZ, MEHMET TUNCAY (SPRINGER HEIDELBERG, 2022)
As an autosomal recessive autoinflammatory disease, treatment of Familial Mediterranean fever (FMF) has still gaps. Clinical studies are proving the safety and efficacy of colchicine in patients with FMF. However, there are very limited data on colchicine-resistant patients treated with canakinumab. This study presents the real-life experience of two rheumatology clinics choosing canakinumab in adult patients with FMF resistant to standard therapy. Treatment-resistant FMF patients with validated diagnoses enrolled from two rheumatology clinics. A special database was generated for the study and patients' demographic characteristics, FMF attack characteristics, adverse events seen during treatment, family history, MediterraneanFeVer (MEFV) mutations, and laboratory results recorded. Patients with missing dates were excluded from the analysis. PRAS score is used to assess the disease activity. A total of thirty colchicine and/or anakinra-resistant patients were enrolled to study. Twenty-one patients were female (70%) and the average disease duration was 21 years. The time from colchicine to anakinra was 4.27 years and the time to canakinumab was 1.52 years. Abdominal pain (100%), fever (93.3%), chest pain (56.7%) were the most prevailed findings. Morning stiffness, myalgia, low back pain, chest pain was the predominant musculoskeletal findings. Median colchicine dose was 2 mg/day (min-max 0.5-3 mg/day). The most common side effect during anakinra treatment, apart from treatment unresponsiveness, was injection site reactions. Before canakinumab treatment, the mean number of attacks was 8.3 in the 24 weeks, 4.33 in the third month of canakinumab treatment, and 1.56 at the last visit (p < 0.001). Also, the mean duration of attacks was 67.20 h before canakinumab treatment, this period decreased to 18.27 h after six months of canakinumab treatment (p < 0.001). Canakinumab is effective and tolerable to reduce attacks in resistant patients with FMF. Laboratory findings and clinical observation reveals that canakinumab can be another treatment option for colchicine and/or anakinra non-responders. Further studies with larger patients are required to validate recent findings with canakinumab.
Keywords: Familial Mediterranean fever; Colchicine resistant; Anakinra; Canakinumab; Biologics